A Femininity against Another. Women, Womanhood and Feminism in Nineteenth-Century African-American Thought - (:unkn) unknown (My University, 2024)
The author explores the articulation of the signifiers « women » and « femininity/womanhood » within the suffragist movement in the United States and nineteenth-century African-American thought. To understand the competing uses of these categories and the experiences or conflicts they cover, the author first looks at white feminists’ reappropriations of the idea of womanhood in the struggle for women’s suffrage and the exclusion of black women (their perspectives, thoughts and experiences) within the suffragist movement. She then returns to the shifts made by African-American activists, orators and intellectuals in the redefinition of an exemplary womanhood, a bearer of universality, destabilizing the criteria for belonging to the women’s group. Drawing in particular on the thought of Anna Julia Cooper (1858-1964), the author aims to highlight the strength of the African-American conceptualization of femininity in the struggle against the intertwined oppressions of gender, race and class, and in the affirmation of a radically transformative politics, beyond the mere demand for suffrage.
Keywords: African Research